A Public Management for all Seasons? - Hood, Christopher
This article discusses: the doctrinal content of the group of ideas known as 'new public management' (NPM); the intellectual provenance of those ideas; explanations for their apparent persuasiveness in the 1980s; and criticisms which have been made of the new doc- trines. Particular attention is paid to the claim that NPM offers an all-purpose key to better provision of public services. This article argues that NFM has been most commonly criticized in terms of a claimed contradiction between 'equity' and 'efficiency' values, but that any critique which is to survive NPM's claim to 'infinite reprogrammability' must be couched in terms of possible conflicts between adminishafive values. The conclusion is that the ESRC'S 'Management in Government' research initiative has been more valuable in helping to identdy rather than to definitively answer, the key conceptual questions raised by NPM.